Yellow mealworm (Tenebrio molitor) meal in diets of grass carp (Ctenopharyngodon idellus): Effects on growth performance, antioxidant capacity, immunity, intestinal morphology, and intestinal microbiota - Linlin Yang; Minglang Cai; Lei Zhong; Yulong Yin; Yonghong Xie; Shouqi Xie; Yi Hu; Junzhi Zhang (Animal Nutrition, 2025)
The impacts of substituting dietary soybean meal (SBM) with yellow mealworm meal (YMM) were investigated during a 56-day feeding trial on growth, antioxidant capacity, immunity, intestinal morphology, and intestinal microbiota of grass carp. A total of 750 grass carp were divided into 5 groups (3 replications per group and 50 fish per replication) with different levels of YMM: SBM (control group), H25, H50, H75, and H100, for 8 weeks. The results showed that dietary YMM significantly increased final body weight (FW), weight gain (WG), and protein efficiency ratio (PER) in H25 group (P < 0.05); however, complete substitution showed the opposite trend (P < 0.05 for FW and WG). The liver antioxidant capacity was improved, manifested by enhanced superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) activities, glutathione (GSH) content and up-regulated antioxidant-related genes mediated by the Keap1-Nrf2 signaling pathway in the H25 group (P < 0.05). However, in the H100 group oxidative stress occurred in parallel with impairment of hepatic function. Intestinal inflammation was aggravated in the H100 group as evidenced by the up-regulated pro-inflammatory gene expression mediated by the NF-κB pathway (P < 0.05). Additionally, the activity of intestinal digestive enzymes for the grass carp was significantly reduced and accompanied with intestinal mucosal barrier dysfunction in the H100 group (P < 0.05). In summary, replacement of SBM with 25% YMM showed positive influences on growth, antioxidant capacity, immunity, and intestinal health. Conversely, complete replacement of SBM with YMM triggered oxidative stress, caused liver function disorder, and impaired intestinal health in grass carp.